Molecular, Epidemiological, and Clinical Investigations of Anaplasma marginale Infection in Cattle at Qena Governorate, Upper Egypt - Ahmed, Abdalrahman; Fereig, Ragab M.; Khalifa, Fatma Ahmed; Mahmoud, Hassan Y.; Ali, Alsagher O. (Journal of Advanced Veterinary Research, 2023)
Bovine anaplasmosis is one of the most important diseases that threaten livestock production worldwide especially in developing countries, in cattle mainly caused by obligate intra-erythrocytic Anaplasma marginale. A. marginale is transmitted biologically by ticks (Hyalomma, Rhipicephalus). Bovine anaplasmosis causes mild to severe clinical signs ranging from anorexia, fever, anemia, and respiratory manifestations to icterus and death. Molecular detection is the best method for Anaplasma diagnosis because of its ability to detect sub-clinical and carrier hosts. This study investigated the occurrence of A. marginale infection among cattle in the Qena governorate utilizing a molecular assay based the msp5 gene. A total of 100 whole blood samples were collected randomly from apparently healthy and diseased cattle. Such cattle were examined clinically, and their samples were included for microscopic examination. PCR screening of the tested cattle showed 23% (23/100) as a positive rate. While 6 samples from 100 (6%) showed A. marginale parasite in the microscopic examination. Several risk factors were analyzed in the current study, higher incidence rates were detected in animals less than 2 years than older than 2 years, Holstein-Friesian breeds than crossbreeds and in animals kept in small farms than in the mass farming system. Clinical and hematological variables were also investigated in several infected and non-infected cattle based on PCR reactivity. Fever, anorexia, respiratory manifestations, enlarged lymph nodes, pale or icteric mucous membranes and digestive disorders were reported in infected cattle (n= 23) but not in non-infected animals (n=77). Consistently, hematological variables in infected cattle (n = 10) revealed significantly lower RBCs count and hemoglobin content than those in the non-infected group (n=20) indicating hemolytic anemia. This study shows the high prevalence of A. marginale in cattle in Qena governorate associated with health hazards and multi-risk factors, so frequent usage of acaricides, regular examination of cattle, and successful chemoprophylaxis are recommended.